1997
DOI: 10.1139/h97-038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Behaviour of Motor Units in the Tibialis Anterior During Voluntary Contractions

Abstract: The present work was carried out to analyse the properties and behaviour of Tibialis anterior motor units (MUs) during voluntary contractions in humans. A total of 528 single MU mechanical properties was recorded in 10 subjects by means of the spike-triggered averaging (STA) technique. MU recruitment thresholds and discharge frequencies were recorded during linearly increasing maximal voluntary contraction (MVC). The results indicate a mean (+/- SD) MU torque of 25.5 +/- 21.5 mN.m. and a mean time-to-peak of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
100
3
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 0 publications
18
100
3
1
Order By: Relevance
“…2 Number of motor units in bands of mean ®ring rates (MFR) in pulses per second (pps). Results from concentric wrist¯exion at two exercise intensities, 30% maximal exercise intensity (MEI) and 60% MEI land-Ritchie and Lippold 1954;Gydikov et al 1978;Dorfman et al 1989;Van Cutsem et al 1997). Also, the present results supported the ®ndings of a number of previous observations of higher ®ring rates when shortening contractions have been compared to static force contractions and therefore may describe a general principle in MU behaviour (Shapkov et al 1977;Andrew 1985;Moritani et al 1988;Ivanova et al 1997).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…2 Number of motor units in bands of mean ®ring rates (MFR) in pulses per second (pps). Results from concentric wrist¯exion at two exercise intensities, 30% maximal exercise intensity (MEI) and 60% MEI land-Ritchie and Lippold 1954;Gydikov et al 1978;Dorfman et al 1989;Van Cutsem et al 1997). Also, the present results supported the ®ndings of a number of previous observations of higher ®ring rates when shortening contractions have been compared to static force contractions and therefore may describe a general principle in MU behaviour (Shapkov et al 1977;Andrew 1985;Moritani et al 1988;Ivanova et al 1997).…”
Section: Discussionsupporting
confidence: 88%
“…It has been suggested that this probably re¯ects a change from a feed-back to a preprogrammed activation pattern when the contraction is too fast to bene®t from aerent information (Desmedt and Godaux 1977). In addition, muscle speci®c recruitment patterns have been demonstrated (Kukulka and Clamann 1981;Van Cutsem et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This can be attributed to the so called age related MU remodelling (McNeil et al, 2005) that creates larger and slower MUs but counteracts the cross-sectional area reduction up to a 50% loss of motoneurons took place (Aagaard et al, 2010). On the average amplitudes of our individual twitches were higher than the values reported by Van Cutsem, Feiereisen, Duchateau, and Hainaut (1997) in their study on single motor units. This may suggest that, as stated by Buchthal and Schmalbruch (1970) the neuromuscular stimulation can activate SBF containing more than one MU.…”
Section: Peak Twitch Amplitudementioning
confidence: 51%
“…In humans the application of invasive methods of single MU activation is not possible and different methods such as the spike triggered averaging during voluntary contraction can be used to extract the single MU mechanical response. In TA McComas and Thomas (1968), Sica and McComas (1971) and Van Cutsem et al (1997) reported CT spectra for pulled slow and fast MU ranging from 20 to 86 ms. These data concerning human CT values stress that the larger is the muscle the longer is the CT of their MUs.…”
Section: Contraction Timementioning
confidence: 99%
“…These frequencies were chosen to cover the range of motor unit discharge rates during slow and fast contractions of the tibialis anterior (Desmedt and Godaux 1977;Van Cutsem et al 1997;Klass et al 2008). Before the subjects performed the conditioning MVC, three responses to a single stimuli (twitch or C 1 ), a twopulse trains (PT 2 ), and a three-pulse trains (PT 3 ), were recorded.…”
Section: Methodsmentioning
confidence: 99%